Hubungan Waktu Tunggu Pasien Dengan Tingkat Kecemasan di Instalasi Gawat Darurat IGD Rumah Sakit X - Uswatun Hasanah (JSN : Jurnal Sains Natural, 2023)
Emergency patient services are services that require immediate, precise and careful help to prevent death and other possibilities. In emergency services, time is very important as time saves lives (time saving is life saving). The purpose of this study was to determine the relationship between patients’ wait-time and the level of anxiety in the Emergency Room (ER) X Hospital. The research design used in this study was analytic research with a cross sectional approach. The samples of the study were the patients in emergency department as many as 101 respondents selected through purposive sampling technique. In order to collect the data, the researcher spread out questionnaire to the samples, and then analyzed them by using rank sperm. The results showed that out of 101 respondents, 75 (74.3%) waited for a short time. Henceforth, they were categorized into the short wait-time category. 26 respondents (25.7%) waited for a long time and categorized into long wait-time 26 respondents. The patients's anxiety level was mostly in the moderate level experienced by 62 respondents (61.4%), and the lowest is in the mild anxiety category, experienced by 18 respondents (17.8%). This could also be seen from the analysis test value of p value that was lower with a significant level of 0.05 then p value <α so that Ha was accepted and H0 was rejected or vice versa. This study could suggest that there was a relationship between patients’ wait-time and the level of anxiety in the Emergency Room at the X Hospital. Therefore, the patients should not stay too long in the ER.